Higher education does not always lead to greater support for democracy - OH, Seonju (KDI School, 2022)
Modernization theory suggests that support for democracy would increase as education levels rise. To empirically examine this claim, this study analyzes the preference for democracy according to the level of education. A sample of 118,618 respondents from the World Values Survey (WVS) is used, covering 26 countries over 10 years. The findings indicate that the importance of democracy, perceptions of political systems, and the state of democracy positively affect support for democracy. Once country and year fixed effects are employed, it found that highly educated individuals are more likely to embrace the concept of democracy, but support for specific democratic policies varied significantly. These results suggest that while education may increase support for democracy as an abstract concept, it does not necessarily translate into support for actual substantive policies to be considered crucial for democratic governance.
Thesis(Master) -- KDI School: Master of Development Policy, 2022
Keywords: Democracy; Public administration